Size Effect in SnO2/Al2O3 Core/Shell Nanowires after Battery Cycling. Issue 11 (20th September 2022) - Bürger, Jasmin-Clara; Lee, Serin; Penn, Aubrey; Gutsch, Sebastian; Kolhep, Maximilian; Büttner, Jan; Fischer, Anna; Ross, Frances M.; Zacharias, Margit
Abstract : Full utilization of the high storage capacity of conversion electrode materials as tin oxide (SnO2 ) in lithium‐ion batteries is hindered by the high volumetric expansion due to the high lithium storability which can lead to major cell damage and consequent safety issues. To overcome this issue, two promising approaches, nanostructures and buffer layers, are combined and evaluated. SnO2 nanowires (NWs) are coated with an aluminum oxide (Al2 O3 ) buffer layer to investigate the combination SnO2 –Al2 O3 . Strong differences in the crystallinity after cycling between the SnO2 /Al2 O3 core/shell NW‐based heterostructure and uncoated SnO2 NWs based on detailed structural analysis are shown via transmission electron microscopy (TEM) and determination of the elemental distribution of tin, oxygen, lithium, and aluminum via energy‐dispersive X‐Ray spectroscopy and energy‐filtered TEM in the as‐prepared and postmortem nanostructures. The core/shell NWs exhibit two different states after charge/discharge cycling, amorphous or crystalline, depending on the NW diameter; for the uncoated SnO2 NWs, only an amorphous postmortem structure is found. Additionally, differences in the elemental distribution for the amorphous and crystalline postmortem SnO2 /Al2 O3 core/shell NWs, especially for tin, are measured. Consequently, the structures and effects of the Al2 O3 coating on the lithiation behavior of SnO2 NW‐based heterostructures are discussed. Abstract : By high‐resolution electron microscopy techniques, as‐prepared and postmortem tin oxide nanowires (SnO2 NWs) and SnO2 /Al2 O3 core/shell NWs are analyzed before and after chronopotentiometric cycling. Depending on the NW diameter, the SnO2 /Al2 O3 core/shell NWs show amorphous and crystalline postmortem structures. Elemental analysis and theoretical discussion give insights concerning the material transformation and failure mechanisms of SnO2 –Al2 O3 ‐based anode materials.